Prevention of anemia is the guarantee of human health - Turdiyeva Odinakhan Ma'mirovna; Toyloqova Iroda Ibrahim's Qizi; Qahhorova Fotimakhan Kamiljon's Qizi (Genius Publishing Group, 2024)
This article contains the necessary information about measures to prevent anemia and the symptoms of anemia. Sources on the importance of correct and rational nutrition in preventing anemia are given
Keywords: Anemia; pregnancy; iron